Boston College daily sleep and well-being survey data during early phase of the COVID-19 pandemic - Tony J. Cunningham (Nature Portfolio, 2021)
Measurement(s) Emotional Well-being • sleep quality • worry measurment • social behavior • Stress • self rated health • Alcohol Consumption • Affective Symptoms • chronotype measurement • Anxiety • Personality Trait • Demographic Data • empathy measurement • COVID-19 Related Memory Questions • self-regulation • Emotion • behavioural disinhibition measurement • response to uncertainty Technology Type(s) Survey • Pittsburgh Sleep Quality Index • Generalized Anxiety Disorder - 7 Questionnaire • Perceived Stress Scale • Patient Health Questionnaire - 9 Item • Positive and Negative Affect Schedule • Ultra Short Munich Chronotype Questionnaire • Cognitive emotion regulation questionnaire (CERQ) • Liebowitz Social Anxiety Scale (LSAS) • Self-Report of Personality • Reduced Morningness Eveningness Questionnaire (MEQ) • Toronto Empathy Questionnaire • Brief Self-Control Scale • Emotion Regulation Questionnaire (ERQ) • Short Impulsive Behavior Scale • Intolerance of Uncertainty Scale Sample Characteristic - Organism Homo sapiens Sample Characteristic - Environment first-order administrative region • human dwelling Sample Characteristic - Location United States of America • Global Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14069348